Women's Rights And Roles Reflected In Larysa Kondracki's The Whistleblower Movie (2011): A Feminist Approach - Wati, Ira Kartika, Dr. Phil. Dewi Candraningrum, S.Pd, M.Ed, Drs. H. Abdillah Nugroho, M.Hum (2013)
The major problem of this study how is women's rights and roles reflected in Larysa Kondracki's The Whistleblower movie (2011). The study is intended to analyze the movie based on structural elements and to analyze the movie based on the feminist approach. The object of this study is The Whistleblower movie by Larysa Kondracki. This study belongs to descriptive qualitative research. There are two types in the data source. First, the primary data is The Whistleblower movie that was released in 2011 and the secondary data are books or any information relation to the practice of women's rights and roles that support the feminist approach. Both data the collected through library research and analyze by descriptive analysis using Feminist approach. Based on the analysis, the researcher draws the following conclusions. First, based on the structural analysis of each element, it explains that the character and characterization, casting, plot, setting, point of view, theme, mise-en-scene, cinematography, sound, and editing are related to each other. Second, based on the feminist analysis, the women's rights, women's roles, women's position, and women participation are reflected in Larysa Kondracki's life. Third, Larysa Kondracki fulfills the characteristic of women's rights and roles that showed in her role the women's rights in society, education, work, politic, and economy.